Effects of aqueous cadmium on embryos and larvae of mirror carp - Calta, M (Indian Counc Agricultural Res, 2001)
This work was an attempt to investigate the effects of various level of aqueous cadmium in egg valume, pigmentation, hatching, growth and survival of mirror carp (Cyprinus carpio L.) embryos and larvae from fertilization to fully resorption of yolk. The volume increase (%) in eggs exposed to 5-50 mg/L of cadmium solution was significantly lower compared with control. The duration of eye pigmentation, body pigmentation and blood coloration remained unaffected by cadmium. The start of hatching time was considerably delayed in 10-50 mg/L of cadmium solution (109-117 hr) compared with the control (78 hr). The proporation of normal hatched larvae was significantly reduced in 5-50 mg/L of cadmium with respect to the control. The proportion of dead and deformed larvae increased with increasing of cadmium concentration in water. The deformities including bead malformation and sipinal curvatures reveal the effect of cadmium on embryonic development. Larval growth (weight and length) was significantly retarded by cadmium above 10 mg/L with respect to the control. The 96-hr LC50 for larvae aged under 5 days, 5-10 days and over 10 days were 3,4 and 6 mg/L of cadmium respectively. The 96-hr toxicity test results showed that the sensitivity of mirror carp larvae to cadmium decreases with increasing of larval age.
Keywords: cadmium; Cyprinus carpio; embryo; larvae; mirror carp